Mesin Pencetak Pelet Vertikal dengan Mini Conveyor - Helme Affataqur Rozaqi, Aghata; Winangsit, Abdilah; Mada Putra, Bima; Khaq, Badrizzul; Rohmandani, Fajar; Dian Santoso, Aris; Fahmi Fahrizi, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
This design is based on the results of observations, literature studies and the development of previous pellet machines. Observations show that the horizontal pellet machine is less efficient in terms of time, because the horizontal pellet machine requires a composition of wet ingredients, wet material will produce wet pellets, so it still requires a long drying time so that the pellets are dry and ready to be packaged, the resulting product even horizontal pellet machine in terms of shape is less flat. To minimize this problem we made a vertical pellet machine, to make our energy efficient we added a mini conveyor so that the operator no longer spends a lot of energy. This vertical pellet machine is equipped with an electric motor powered by 1 HP or 746 watts, a gear box of 1: 60, a conveyor with a height of 165 cm, a mold plate of 3 mm - 10 mm, a hoper with a diameter of 60 cm and a roller with a diameter of 3 cm - 10 cm. So it can produce 120 kg/hour pellets.